Seasonal and Spatial Patterns of Ecotoxicological Indices of Trace Elements in Superficial Sediments of the Marchica Lagoon Following Restoration Actions during the Last Decade - Bouchra Oujidi; Mohammed El Bouch; Mounia Tahri; Mostafa Layachi; Soilam Boutoumit; Rachid Bouchnan; Hassan Ouahidi; Moussa Bounakhla; Najib El Ouamari; Mohamed Maanan; Hocein Bazairi; Nadia Mhammdi; et al. (Diversity, 2021)
Marchica Lagoon, a Ramsar site on the Mediterranean coast of Morocco, is experiencing the impacts of watershed pollution, which includes pollutants from the domestic, agricultural, industrial, and mining sectors. Restoration actions were undertaken around this lagoon during the last decade in order to protect its ecological value and to develop tourist activity. To conserve the biodiversity in the lagoon, it is important to assess the environmental state of this ecosystem. This study aims to evaluate the ecotoxicological state of sediments through the post restoration characterization of the trace elements Pb, Cu, Zn, Cr, Co, and Ba, as well as their correlation to the major elements, grain size, and total organic carbon, sampled during two campaigns (the wet and dry seasons of 2018) across a sampling network of thirteen stations. Multivariate analysis and ecotoxicological risk assessment of the trace elements using the sediment quality guidelines and five pollution indices (geoaccumulation index (Igeo), enrichment factor (EF), contamination factor (CF), pollution-load index (PLI), and mean effect range median quotient (m-ERM-Q)) revealed contamination of the lagoon by Pb, Zn, and Cu, and minimal pollution by Cr, Co, and Ba. The distribution of the biological-risk index reveals that four zones of the lagoon may present a high probability of toxicity, thus constituting potential risk areas for aquatic organisms: during the wet season, the area in the northwestern sandbar border, the southwest eutrophication zone, and the mouth of the stream valley conveying industrial discharges; and during dry season, the northwestern eutrophication zone. Despite the restoration actions achieved around the lagoon, the lead, zinc, and copper concentrations increased, and their variation was significant between group stations. The biodiversity conservation of Marchica Lagoon requires continuous monitoring and assessment, as well as the implementation of an integrated management plan with restoration actions, not only around the lagoon, but also at its watershed level.